Policy implications of contemporary labeling theory research - Kavish, Daniel Ryan (2017)
Labeling theory is a criminological theory that contends that formal sanctions amplify, rather than deter, future delinquent and criminal behavior. This paper identifies and describes some of the policies and programs that labeling theorists suggest would be effective at reducing delinquency and crime, or at least mitigate the effects of negative labeling experiences. The findings of contemporary examinations of juvenile delinquency and crime are briefly reviewed to provide the context for a variety of proposed policy implications. Programs such as family counseling, the Inviting Convicts to College Program, and Multisystemic Therapy are highlighted, and the importance of promoting education and employment for labeled individuals is discussed.